Pemberdayaan Masyarakat Dengan Program Pembagian Bibit Tanaman Dalam Upaya Penghijauan Lingkungan Dan Meningkatkan Perekonomian Di Desa Lubuk Sakai, Kec. Kampar Kiri Tengah, Kab. Kampar - Syarifa Ulayya; Irwin Mirza Umami (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Kukerta activities are activities in the form of community service that aims to foster a sense of concern for the community. Lubuk Sakai Village is one of the villages located in Kampar Kiri Tengah District, Kampar Regency, Riau Province. One of the problems found in Lubuk Sakai Village is suboptimal land use. This is characterized by the use of land that is only used as oil palm plantations. From these problems, the Kukerta activity of Riau University aims to optimize land use in Lubuk Sakai Village with a work program for the distribution of plant seeds in an effort to green the environment while encouraging the economy of the surrounding community. The methodology of the service carried out is the delivery of seed application letters to the Head of the Riau Provincial Environment and Forestry Service, the pick-up of BAP letters at the Riau Provincial Environment and Forestry Service, the collection of plant seeds in Lubuk Sakat Village and counseling as well as the distribution of plant seeds at the Lubuk Sakai Village Head Office. The results show that there are 100 plant seeds namely durian, mahogany, and petai that will be distributed to the community. Judging from the response of the community, it looks enthusiastic in this activity. The distribution of plant seeds is expected to make land use more optimal in order to achieve environmental greening and improve the economy of the community in Lubuk Sakai Village.